Towards a multiversity? Universities between global trends and national traditions - Krücken, Georg; Kosmützky, Anna; Torka, Marc (Transcript, 2007)
All over the world new ideas and models emerge on how to organize the higher education sector and its institutions. The contributions in this volume identify the most influential transnational models and investigate their origins and mechanisms of dissemination as well as the resulting consequences for national systems. Will global trends in higher education lead to homogeneity or will they result in an increased differentiation? This question is addressed by higher education researchers with very different disciplinary and national backgrounds. Contributors are, among others, Jürgen Enders, John W. Meyer, Christine Musselin and Kerstin Sahlin-Andersson.
OCLC: 237124776